PENGARUH KECERDASAN EMOSIONAL, MINAT BELAJAR DAN PERILAKU BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTANSI - Luh Gede Ega Yuniantari (Hita Akuntansi dan Keuangan, 2021)
This studi aims to determine the influence of emotional intelligence, learning interests and learning behaviors on the level of accounting understanding. The research was conducted on students of Accounting Studi Program class of 2018. There were 139 samples. The ianalysis itechnique used is iMultiple iLinear Regression Analysis, ithe iresults of the studi ifound ithat iemotional iintelligence iand ilearning iinterests ihave a positive and significant ieffect ion ithe ilevel iof iaccounting iunderstanding. Meanwhile, ilearning ibehavior has no effect on the level of accounting understanding.